Malignant gastroduodenal obstruction: retrospective comparison of endoscopic and surgical palliative therapy - Rudolph, Hans Ulrich; Post, Stefan; Schlüter, Michael; Seitz, Uwe; Soehendra, Nib; Kähler, Georg (Scandinavian journal of gastroenterology, 2011)
Introduction. Endoscopic stenting (ES) is a minimally invasive alternative to surgical gastroenterostomy (GE) for palliation of malignant gastroduodenal obstructions. This consecutive, retrospective analysis compares the clinical outcome of all patients undergoing ES or GE in the same period. Methods. ES was performed at the Endoscopy Department, University Hospital Mannheim or at the Interdisciplinary Endoscopy Department, University Hospital Hamburg-Eppendorf. GE was performed at the Surgical Department, University Hospital Mannheim. All palliative ES or GE on patients with malignant gastroduodenal obstruction without earlier gastric resections between January 2001 and April 2007 were evaluated. Main outcome measurements were ability of solid food intake (gastric outlet obstruction score), persistence of nausea and vomiting (gut function score), length of hospital stay, morbidity, mortality and re-interventions. Results. A total of 44 ES and 43 GE were performed. Nausea and vomiting - measured by means of the gut function score - persisted in significantly more patients in the GE group than in those who underwent stent placement (p = 0.0102). The gastric outlet obstruction score at discharge from the hospital revealed no significant difference in the ability of solid food intake between the groups. The hospital stay was significantly longer in the GE group (p = 0.0003). There was no significant difference in mortality and the rates of complications and re-interventions. Conclusion. In this study, ES is a generally equivalent - and in several points superior - alternative to GE for palliation of malignant gastroduodenal obstruction. ES seems to be the less invasive alternative for symptomatic patients. GE has good results in patients with longer survival and can be practiced within abdominal explorations.
Gesehen am 05.04.2022